Evaluation of the Clinical Outcome of Nab-paclitaxel on Multiple Primary Malignancies: A Systematic Review and Meta-analysis - Fatemeh Salehi Kahrizsangi; Neda Mehrafar; Pezhman Ghadami; Fatemeh Rabiee; Yasaman Shariati (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2022)
Background and aim: In the present study, an attempt has been made to analyze the side effects of nab-paclitaxel compared to sb-paclitaxel and docetaxel. The present study aimed to evaluate the clinical outcome of Nab-paclitaxel on Multiple primary malignancies.Material and methods: All articles published in international databases such as PubMed, Scopus, Science Direct, ISI Web of knowledge, and Embase between 2012 to July 2022 are included. 95% confidence interval on odds ratio were done with the fixed effect model and Mantel-Haenszel method. Meta-analysis data collected from selected studies were performed using Stata/MP.V17 software.Results: In the initial review, duplicate studies were eliminated, abstracts of 311 studies were reviewed, two authors reviewed the full text of 43 studies, and finally, nine studies were selected. The odds ratio of treatment termination and treatment delay due to adverse events between Nab-paclitaxel and the control group was 0.72 (OR, 95% CI 0.53, 0.92; p=0.00) and -0.52 (OR, 95% CI -0.69, -0.35; p=0.00). The odds ratio of deaths due to treatment-related adverse events between Nab-paclitaxel and the control group was 0.37 (OR, 95% CI 0.11, 0.63; p=0.01).Conclusions: According to the present meta-analysis, hematological and non-hematological side effects were higher in the group receiving nab-paclitaxel compared to the group receiving sb-paclitaxel and docetaxel.